Economic modernization in a Chepang Village in Nepal - Gurung, Ganesh Man (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1067 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.32-39